Performance of Choline-Based Deep Eutectic Solvents in the Extraction of Tocols from Crude Palm Oil - Hadi, N.A.; Ng, M.H.; Choo, Y.M.; Hashim, M.A.; Jayakumar, N.S. (Springer Verlag (Germany), 2015)
Deep eutectic solvents are emerging green solvents that have potential in many separation processes. This study investigates the performance of choline-based deep eutectic solvents in the extraction of tocopherols and tocotrienols (collectively known as tocols) from palm oil, a major natural source of tocols. Deep eutectic solvents comprised of choline chloride salt and selected carboxylic acids as hydrogen bond donors were prepared and used in the extraction of tocols from crude palm oil by liquid-liquid extraction. Tocols concentration in the extracted product was at least double that in the control (8671 mg/kg compared to 3285 mg/kg, respectively). Increasing the amount of the deep eutectic solvents increased the tocols concentration in the extracted product up to 18,525 mg/kg, but the yields lowered from 4 % to less than 1 %. The tocols profile was significantly improved by the increase of the tocotrienols fraction in the products from 80.8 to 99.8 %. This study showed that unique interaction between the selected deep eutectic solvents with the tocols make it possible to selectively separate individual tocols in palm oil, where products with fractions rich in tocotrienols and low in tocopherols (particularly alpha-tocopherol) are favorable.